RECOVERY OF NON-FERROUS PARTICLES FROM RECYCLING NEON LAMPS BY MAGNETIC INDUCTION SEPARATOR - Kadri, Nadjib; Krika, Wafa; Ayad, Ahmed Nour El Islam; Rouibah, Tahar; Ahmet, Fevzi Bozkurt; Kadir, Erkan; Bara, Ilies Rezzag; Ghoneim, Sherif S. M. (EDITURA ACAD ROMANE, 2024)
The use of lamps worldwide is rapidly increasing, and the number of broken, burned-out, and defective lamps is very significant, polluting the environment. For this reason, we will address the topic of lamp recycling using magnetic induction technology. This paper presents induction separation by an innovative, improved induction separator design with an important advantage. It extracts aluminum particles from a mixture of waste materials, including non-metallic and non-ferrous particles from broken neon lamps. The induction separator features a single vertical disk rotated by an electric motor. The disk has a series of permanent magnets mounted alternately on its surface. The experimental results of the separation process achieved through an induction separator exhibit a high purity level, boasting a 100% separation efficiency, surpassing the performance of previous separators. These findings substantiate the validity of employing the induction to conductive materials.
Keywords: Induction; Lamps; Lorentz; Magnetic; Neon; Recycle; Separator; EDDY-CURRENT SEPARATION; Engineering